(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2021)
Background: Functional activity is an important aspect of normal human function. Limited functional activities due to in sciatica have been shown to predispose a person to several restrictions in function and significantly affect the normal daily life. Objective: To determine and compare the effectiveness of Neurodynamic Slider Technique (NST) with conventional therapy (CT) and conventional therapy alone in sciatica for improving functional ability and pain. Method: 40 subjects with sciatica were allocated into two groups (20 subjects in each group). The outcome measure used was Oswestry Disability Index (ODI) and Visual Analogue Scale (VAS). Subjects of group A were treated with Conventional therapy only, whereas the subjects of group B were treated with Neurodynamic slider technique. For both the groups, the technique was performed three times a week for a total treatment period of four weeks. Results: The results demonstrated significant improvement in functional ability for subjects of group B when compared with those of group A (P<0.05) at the end of four weeks. Conclusion: The study shows that CT along with NST are efficient in the rehabilitation of sciatica patients reflecting the improvement of functional ability by reducing pain and considerably increase the physical performance of patients in their own aspects. Thus, Neurodynamic Slider technique along with Conventional therapy can be used in clinical practices for the treatment of sciatica.